Excess‐heat recovery and promotion through organic chemical heat pumps - Silva, Luís António Pinela da (2021)
Heat recovery and promotion is essential to decarbonization, and chemical heat pumps based on reversible organic reactions can aid to fulfil this. This paper stud ied the isopropanol/acetone/hydrogen (IAH) and the tert-butanol/isobutene/water (tB/iB) systems regarding their performance and economic competitiveness through simulation and found that the IAH presents satisfactory performance and has the potential to be a very promising solution in increasing the overall energy efficiency while also preventing the emission of massive amounts of CO2 and other greenhouse gases released during energy production and transforma tion. This system presents enough arguments to become a very successful solution if proper politico-economic support and incentives are established and put into practice.